Customer emotion and impulse buying: the variables that influence repurchase intention / Amiril Azizah ... [et al.] - -, Amiril Azizah; Batoteng, Hendrik; Hariyadi, Sugeng; Barus, Faisal; -, Surahman; Gunawan, Ferdi (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
This study explored customers’ emotion characteristics that predict and influence purchase intention. The study sought to understand customers’ emotional responses and how they affect their purchase decisions. Results showed a positive correlation between factors and purchasing intention. A sample of recent buyers at Miniso store was used for the research. The data comprised customer emotions, perceived value, product quality, brand image, and satisfaction. Regression analysis was used to find purchase intention predictors. This study found that customers’ emotions influence purchasing intention. Happy, excited, and satisfied customers are more likely to buy. Perceived value, product quality, and brand image also affect buyers’ emotions and purchasing intentions. The ramifications for organizations and marketers are significant. Companies can modify their marketing efforts to inspire pleasant emotions and increase buying intent by knowing customers’ emotions and purchase intention. This is possible through brand positioning, product quality management, and customer journeys that evoke good feelings.